Supraclavicular Brachial Plexus Block with or without Dexamethasone - Furkan Hyder, Madiha Raza, Hasan Ali Shah, Adeel Hussain, Noor-Us-Saba, Syed Farjad Sultan (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the effect of supraclavicular brachial plexus block in patients with or without dexamethasone. Study design: Double blind randomized controlled trial Place and duration of study: Department of Anesthesia and Critical Care, The Indus Hospital a free of cost tertiary care hospital in Karachi from 9th May 2019 to 19th February 2020. Methodology: Sixty patients were enrolled with 30 patients in each intervention group. Patients who came for elective or emergency surgery of the upper limb below shoulder were included in the study. Block performed on patients lying supine at 45 degree. The dexamethasone group received 0.25% plain bupivacaine 18 ml with 2ml dexamethasone (0.4mg/ml) and control group received 0.25% plain bupivacaine 18 ml with 2 ml normal saline. Results: The age of the group B patients was higher than the group A patients such as 43.4±15.7 years vs 38.6±14.2 years. The ASA level presented higher scoring than II in patients from Group B with 63.3% those patients who called for pain. In this study the intra operative vital signs showed an insignificant variance in both groups.However, a significant increase in duration of analgesia was observed in group A. Conclusion: Perineural administration of dexamethasone with clinical bupivacaine concentration can prolong the duration of anesthesia.